Review of Naturopathy of Medical Mushroom, Ophiocordyceps Sinensis, in Sexual Dysfunction - Jiraungkoorskul, Kanitta; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Sexual dysfunctions including desire, arousal, orgasm, and pain disorders are increasing worldwide due to etiological factors and aging. Several types of treatment are claimed in modern medicine, but they have serious side effects and higher costs. In fact, alternative approaches, such as the intake of plants, fungi, and insects, or their extracts, have also been practiced to enhance sexuality and ameliorate illness with notable successes. However, the scientific evidence related to the mechanisms and efficacy of these alternative medicines is both scarce and all too often unconvincing. Ophiocordyceps sinensis is an Ascomycetes fungus parasitic to Lepidoptera larvae, and has long been used as medicine to treat many illnesses and promote longevity in Chinese society. Previous investigations have shown that O. sinensis has many pharmacological activities. This review has focused on illustrating that O. sinensis can enhance libido and sexual performance, and can restore impaired reproductive functions, such as impotency or infertility, in both sexes.
Keywords: Aphrodisiac; fungi; mushroom; Ophiocordyceps sinensis; sexual dysfunction